The Concept of Time and the Future Perception of Zionism Based on the Messianic Doctrine: Forcing God into the Golden Age - Semiha Karahan (Milel ve Nihal)

(untitled)
The doctrine of the Messiah in Judaism is a fundamental tenet of faith and the central pillar of Jewish eschatology. The belief that the Messiah will come in the end times to deliver the Jewish people has profoundly influenced Jewish sociology, psychology, and politics. In Jewish theology, time is linear and limited to 6,000 years, which also corresponds to the Hebrew calendar. This concept of finite time, combined with Messianic belief, has shaped the Jewish perspective on history and instilled a deep significance in the calendar. The Hebrew calendar illuminates both the Jewish past and, through the Messianic doctrine, their anticipated future. Jews believe they once experienced a golden age under the Kingdom of David and will live through a similar golden age in the future with the arrival of the Messiah, a descendant of David. Throughout the diaspora, Jews have awaited the Messiah, placing their hopes in this promise. By the 19th century, Zionism emerged, offering Jews the promise of redemption. Taking on aspects of the Messiah's role, Zionism provided a path of salvation through immigration to Palestine and the establishment of a Jewish state. Except for Religious Zionism, Zionists generally avoided aligning their ideology with Messianic beliefs. However, Religious Zionism framed itself as part of the Messianic deliverance. As Zionism achieved its objectives in Palestine, Religious Zionism began to radicalize, giving rise to Messianic Zionism. Messianic Zionism is apocalyptic, militant, radical, Kabbalistic, war-oriented, and aims to accelerate the end by interpreting contemporary events as the fulfillment of prophecies. Radical Messianic Zionists, believing that all prophecies must be fulfilled by human action for the Davidic Messiah to arrive, use mystical calculations to assert that the end is near. As a result, they pressure the State of Israel to engage in bloodshed and initiate war, seeing these actions not as choices but as essential conditions for Messianic Zionism.